1930
DOI: 10.1021/ja01367a001
|View full text |Cite
|
Sign up to set email alerts
|

THE STRUCTURE OF GELATIN GELS FROM STUDIES OF DIFFUSION1

Abstract: The behavior and properties of gelatin systems have been the subject of a good deal of study by colloid investigators because they serve as a prototype of gel-like bodies occurring in living organisms. Further studies into the mechanism and necessary conditions for gel formation, the structure and characteristic properties of gels, and the changes in state which gels undergo should throw much light onto related biological problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1952
1952
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…This is in accordance with the findings of Smidsrød and Skjåk-Braek (1990) concerning alginate gels. However, these observations were made by experiments conducted either with agar or alginate gels which are characterized by different microstructure, while other authors reported that diffusion of low molecular weight substances like glucose in gelatin gels was affected by varying the polymer concentration (Friedman & Kraemer, 1930;Hendrickx, Ooms, Engels, Pottelbergh, & Tobback, 1987). Theys et al (2008) also concluded that oxygen limitations (decrease in the oxygen diffusion rate) may account for the drop in μ max of S. Typhimurium.…”
Section: Effect Of Glucosementioning
confidence: 99%
“…This is in accordance with the findings of Smidsrød and Skjåk-Braek (1990) concerning alginate gels. However, these observations were made by experiments conducted either with agar or alginate gels which are characterized by different microstructure, while other authors reported that diffusion of low molecular weight substances like glucose in gelatin gels was affected by varying the polymer concentration (Friedman & Kraemer, 1930;Hendrickx, Ooms, Engels, Pottelbergh, & Tobback, 1987). Theys et al (2008) also concluded that oxygen limitations (decrease in the oxygen diffusion rate) may account for the drop in μ max of S. Typhimurium.…”
Section: Effect Of Glucosementioning
confidence: 99%
“…Friedman and Kraemer (1930) first suggested that the reduced diffusivity in fine pores resulted from increased frictional drag on the solute as a result of the proximity of the solid walls, and for a quantitative estimate they employed the first-order solution of Ladenburg (1907) for the axial sedimentation of a hard sphere through a continuum bounded by a rigid cylinder. Pappenheimer et al (1951) combined this factor with Equation (3) for the partition coefficient.…”
Section: Background and Previous Studiesmentioning
confidence: 99%
“…These were measured by the method of Friedman & Kraemer (1930). I n this method a layer of agar gel is formed in a cylindrical container, and an equal volume of liquid is placed above it.…”
mentioning
confidence: 99%